Back to historical views, reconstructing the sociological imagination: The new tradition of classical and historical studies in the modern Chinese transformation. (January 2017) - Qu, Jingdong
Historical perspectives are a means of reconstructing the sociological imagination, as classical sociologists did. There are many historical dimensions in Karl Marx's social studies: dialectical analysis of the present as history; reconstructed narratives of historical events; and finally, evolution of family, ownership, state, and social formations. Likewise, in order to understand the reality of Chinese society, we need to examine the transformation of modern Chinese social thought and its contexts. By reinterpreting the Theory of the Three Epochs from the classic Spring and Autumn Annals, Kang Youwei proposed that the establishment of the Idea of Cosmic Unity as the universal value for world history and the building of the Confucian religion for the cultivation of mores had resulted in the successful transformation of Chinese society from the Era of War to the Era of Peace. In contrast, Zhang Taiyan upheld the tradition of 'Six Classics are all Histories' and furthered the academic change of focus from classics to history, which Wang Guowei and Chen Yinque carried out. Through the method of synthetical deduction in the social sciences, Wang Guowei interpreted classics historically in Institutional Change in the Yin and Zhou Dynasties, confirming the original principle of the Zhou regime and etiquette on the basis of the patriarchal clan system and its emphasis on law, mores, and institutions. On the other hand, Chen Yinque thoroughly investigated the Middle Period of Chinese history from the perspectives of concourse and inter-attestation and outlined a historical landscape of interfusion between Hu and Han nationalities, the mixing of various religions, the migrations of diverse groups, and the integration of different cultures and mores. In short, there are two waves of intellectual change in the Chinese modern transformation, which together have established the new discipline of Classical and Historical Studies as well as the subsequent institutional and spiritual sources of social and political construction.